Robust preclinical evidence in somatic cell genome editing: A key driver of responsible and efficient therapeutic innovations. Issue 10 (October 2021) - Bittlinger, Merlin; Schwietering, Johannes; Strech, Daniel
Highlights: Somatic cell genome editing (SCGE) is highly promising for therapeutic innovation. Drug development based on SCGE depends on reproducible preclinical evidence. Most SCGE publications do not report on established or new standards for reproducibility. Established standards include reporting randomization, blinding, sample size calculation, and data handling. New standards include requirements for conducting multi-center studies and independent confirmation. Abstract: Somatic cell genome editing (SCGE) is highly promising for therapeutic innovation. This study demonstrates that the majority of 46 preclinical SCGE studies discussed in reviews as particularly promising for clinical translation do not report on key elements for robust and confirmatory research practices: randomization, blinding, sample size calculation, data handling, pre-registration, multi-centric study design, and independent confirmation. We present the here-examined reporting standards and the new National Institutes of Health (NIH) funding criteria for SCGE research as a viable solution to protect this promising field from backlashes. We argue that the implementation of the novel methodological standards provides the opportunity for SCGE research to become a lighthouse example for trustworthy and useful translational research.